Sintesis dan Karakterisasi Silika Aerogel sebagai Adsorben Tumpahan Minyak - Mahardhika, Muhammad Khaishar; Muldarisnur, Mulda (Jurnal Fisika Unand, 2021)
Silica aerogel made from basic sand beach has been synthesized with addition surface modifier agent trymethylchlorosilane (TMCS) as an absorben oil spill. This study has purposed for to analysize addition of TMCS to aerogel silica charateristic. Aerogel silica has been syntesized using sol-gel methode and ambient pressure drying methode (APD). Waterglass is synthesized by melting sea sand and NaOH solution. Waterglass is converted into a gel by adding acetic acid and ammonium hydroxide. Silica gel formed then dried and soaked in methanol to get alcogel. Alcogel then soaked with TMCS : Hexana : Methanol as long 24 hours at 50 oC , Subsequently soaked in a hexane solution and then dried to produce an aerogel The chracterization has been done are oil absorption capacity, porosity, functional group analysis, contact angel test, and silica aerogel morphology analysis. The highest oil absorption capacity is 5 time by it dry mass and highest porosty has been got is 31,5 %. Functional group analysis show the absorption pick on the wave number 789,86 cm-1 which shows the vibration-OSiCH3 and the wave number 549,72 cm-1 which shows the vibration –Si(CH3)3. From the contact angle test, the highest value was 92.5o, which indicated that the silica airgel was not yet hydrophobic. On morphology surface analysis using SEM has been got the size of particel 10,513 µm and 14,244 µm for volume ratio 1:1:1 and 2:1:1.